Increasing Employee Performance Through Physical Work Environment and Work Motivation - Rahman, Robbi Saepul; Nurdiansyah, Haris; Sidharta, Iwan; Purana, R. Deni; Hendiky, Ferry (Journal of Economics, Management, and Entrepreneurship, 2024)
Uncomfortable workstations, inadequate lighting, or improper seating can lead to physical discomfort, less motivation, reduced productivity, and decreased employee performance. This research strives to determine to what extent the impact of the physical work environment in the workplace and encouraging work motivation can improve employee performance.The author's research approach uses quantitative surveys at one of the government agencies in West Bandung. Respondents are 77 state apparatus employees. Data was collected using a structured questionnaire, which was then tested for the validity and reliability of the research instrument. The author's data testing uses path analysis.The research results show that the physical work environment, such as comfortable workstations and adequate lighting, can improve employee performance. Work motivation, such as the desire to develop, impacts employee performance. Research implications indicate that the presence of comfortable workstations and fulfilling employees' desires for development can contribute to increasing employee performance. The research results contribute to a deeper understanding of the role of the physical work environment and employee work motivation to provide positive aspects for the organization to achieve goals.The author is aware that this research only uses survey data. Hence, there are several areas for improvement where the scope of the research could be more extensive and only focused on employees who work in government agencies. Also, this research only discusses the physical work environment in the workplace, encouraging work motivation and employee performance.